The effect of active warm-up and stretching on the flexibility of adolescent soccer players - Zakas, A.; Grammatikopoulou, M. G.; Zakas, N.; Zahariadis, P.; Vamvakoudis, E. (The Journal of Sports Medicine and Physical Fitness, 2006)
Aim: The purpose of the investigation was to examine in field conditions the acute effects of passive stretching after a general warming-up bout as well as the effects of passive stretching alone. Methods: Eighteen adolescent team soccer players participated in this study performing 3 different flexibility-training protocols in separate training sessions. In the first treatment stretching protocol a general warm-up was performed where subjects jogged for 20 minutes. The second treatment stretching protocol consisted of the same general warm-up followed by passive stretching of the lower extremities and the trunk, whereas the third and final treatment stretching protocol consisted of passive stretching alone, without any jogging. Passive range of joint motion was examined in hip flexion, hip extension, hip abduction, ankle dorsiflexion, knee flexion and trunk flexion using a goniometer and a flexometer. Results: The general warming-up session induced a significantly increased range of motion only at the ankle dorsiflexion joint (P<0.05). Results also suggest that passive stretching alone and passive stretching after a general warming-up bout both induced a significantly increased range in all lower extremity joints and trunk flexion (P<0.001). Conclusion: Improvements in flexibility are observed after passive muscle elongation, irrespective of warming-up.